Abundance of Plankton Types and Diversity in The Water of Teluk Nare, North Lombok - Wulandari, Dwi Januar; Larasati, Chandrika Eka; Paryono, Paryono (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Teluk Nare, situated in North Lombok Regency, is a coastal region abundant in marine resources, serving as a hub for fisheries and marine tourism. This research seeks to evaluate the abundance and diversity of plankton as a measure of the ecological health of Teluk Nare’s aquatic environment. Sampling was conducted in February 2025 across ten stations using the purposive sampling technique. Water samples were collected with a plankton net, preserved using Lugol’s solution, and analyzed at the University of Mataram’s Hydrobiology Laboratory. The findings revealed 18 plankton genera from seven classes, with Coscinodiscus, Copepoda, and Nauplius being the most prevalent across all stations. Plankton abundance ranged from 12,000 to 32,333 cells per liter, with the highest concentrations observed near river estuaries. The diversity index indicated moderate levels (1.67–2.08), the evenness index was high (0.71–0.89), and the dominance index was low (0.16–0.26), suggesting no single dominant species and a relatively stable ecosystem. Factors such as currents, salinity, and water transparency were found to influence plankton distribution and abundance. These results offer valuable insights for the sustainable management of Teluk Nare’s coastal ecosystem.